Thermal architecture for the QUBIC cryogenic receiver - May, A. J.; Chapron, C.; Coppi, G.; D’Alessandro, G.; de Bernardis, P.; Masi, S.; Melhuish, S.; Piat, M.; Piccirillo, L.; Schillaci, A.; Thermeau, J. P.; Bonaparte, J.; et al. (Society of Photographic Instrumentation Engineers, 2018)
Fil: May, A. J.. University of Manchester; Reino Unido